Hick's law for choice reaction time: A review. Issue 6 (June 2018) - Proctor, Robert W; Schneider, Darryl W
In 1952, W. E. Hick published an article in the Quarterly Journal of Experimental Psychology, "On the rate of gain of information." It played a seminal role in the cognitive revolution and established one of the few widely acknowledged laws in psychology, relating choice reaction time to the number of stimulus–response alternatives (or amount of uncertainty) in a task. We review the historical context in which Hick conducted his study and describe his experiments and theoretical analyses. We discuss the article's immediate impact on researchers, as well as challenges to and shortcomings of Hick's law and his analysis, including effects of stimulus–response compatibility, practice, very large set sizes and sequential dependencies. Contemporary modeling developments are also described in detail. Perhaps most impressive about Hick's law is that it continues to spawn research efforts to the present and that it is regarded as a fundamental law of interface design for human–computer interaction using technologies that did not exist at the time of Hick's research.